Effect of Hydrocolloids as Emulsifiers on Nutrients, Antioxidants, and Chocolate Melting Point of Almond Milk (Prunus dulcis) - Zulfa, Fitriyah; Rochmah, Alfi Nur; Abdi, Yenny Febriana Ramadhan; Suleman, Dininurilmi Putri; Nadhilah, Dini; Rizki, Prajwalita Rukmakharisma; Dewi, Ella Ela Puspa Dewi; Putri, Kurnia Risda; Aini, Syah ZInda; Alya, Zahra Nur (Fakultas Pertanian Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the effect of using lecithin, carrageenan, and xanthan gum emulsifiers on the physicochemical characteristics of almond chocolate. Three treatments with different emulsifiers were applied, and parameters analyzed include ash, fat, protein content, antioxidant activity, melting point, and organoleptic tests. The results indicated that lecithin provided the highest ash and fat content. Xanthan gum produced the highest protein content, while carrageenan showed the best antioxidant activity. In terms of the melting point, chocolate with xanthan gum had the highest value, while chocolate with carrageenan melted more easily. Organoleptic tests revealed that chocolate with lecithin scored highest in taste, aroma, and texture. In conclusion, the type of emulsifier significantly affects the physical, chemical, and sensory quality of almond chocolate. Keywords: Almond chocolate, emulsifier, lecithin, carrageenan, xanthan gum